EFFECTS OF CARVEDILOL AND METOPROLOL ON VEGETATIVE REGULATION OF HEART AND MICROCIRCULATION IN PATIENTS WITH HYPERTENSION AND HIGH BODY MASS - A. R. Kiselev; V. I. Gridnev; A. S. Karavaev; O. M. Posnenkova; V. A. Shvarts; V. I. Ponomarenko; M. D. Prokhorov; B. P. Bezruchko (Рациональная фармакотерапия в кардиологии)
Aim. To study effects of carvedilol and metoprolol on vegetative regulation of heart and microcirculatory vessels in patients with arterial hypertension (HT) of 1-2 degrees and high body mass/obesity.Material and methods. Patients with HT of 1-2 degrees (n=25; aged 51±8 y.o.) were included in the study. Registration of 0,1 Hz-fluctuations in heart rhythm variability and microcirculation change was performed during passive orthostatic test at spontaneous breath (duration of each test stage 10 min). Synchronization of 0,1 Hz-rhythms was estimated by calculation of phases difference and a numerical measure of synchronization. Frequency estimations of heart rhythm variability spectrum were performed in high and low frequency ranges additionaly.Results. Carvedilol and metoprolol have the comparable antihypertensive effect and influence on vegetative regulation of cardiovascular system in patients with HT. Both drugs have negative influence on synchronization of 0,1 Hz-rhythms in initially high systolic blood pressure level (>150 mm Hg).Conclusion. Carvedilol and metoprolol have comparable influence on synchronization of 0,1 Hz-rhythms in cardiovascular system.